Effectiveness of Tobacco cessation interventions in Maharashtra: A study protocol - Gawde, Nilesh; Fulzele, Punit; Chaudhary, Sonali; Saxena, Deepak; Bharadwaj, Pankaj; B, Unnikrishnan; Gaidhane, Abhay M; Zahiruddin, Quazi Syed (International Journal of Psychosocial Rehabilitation, 2020)
Tobacco use continues to be a major public health concern globally and in India. India has instituted multiple interventions to reduce use of tobacco and offer help to tobacco users to quit under its National Tobacco Control Programme. Reach of its interventions to the population especially tobacco users as been a concern. Although all key interventions are known to be effective and have been tested under experimental conditions as in randomised controlled trials, effectiveness remains to be studied under programmatic and pragmatic conditions. The study design is mixed methods with qualitative as well as quantitative components. Quantitative component shall utilise data from Global Adult Tobacco Survey (GATS) to understand reach of public health interventions. Individuals will then be classified into specific ‘exposed’ groups based upon the combination of intervention received by them including ‘no intervention received’. Comparison of quitratios acrossspecific intervention groups shall help identify most effective intervention under practical considerations. The quit ratios shall be useful for the national programme to determine its strategies.